Geochemical characteristics of zircons in the Ashizuri A‐type granitoids: An additional granite topology tool for detrital zircon studies. (3rd August 2017) - Sawaki, Yusuke; Suzuki, Kazue; Asanuma, Hisashi; Okabayashi, Satoki; Hattori, Kentaro; Saito, Takuya; Hirata, Takafumi
Abstract: Zircon is resistant to alteration over a wide range of geological environments, and isotopic ratios within the mineral provide constraints on ages and their parental magmas. Trace element compositions in zircon are also expected to reflect those of their parent magmas, and have a potential as essential indicators for their host rocks. Because most detrital zircons that accumulate at river mouths are derived primarily from granitoids, the classification of zircon within granitoids is potentially meaningful. This study employs the conventional classification scheme of granites (I‐, S‐, M‐, and A‐types). To clarify geochemical characteristics of zircons in A‐type granites, trace element compositions of zircons extracted from the A‐type Ashizuri granitoids were examined. Zircons from the Ashizuri granitoids commonly show enrichments of heavy rare earth elements and positive Ce anomalies, indicating that these zircons were igneous in origin. In addition, zircons in these A‐type granites are characterized by enrichments of Nb, Y, Ta, Th, and U and strong negative Eu anomalies, which exhibit good positive correlations with those in their whole rocks. This fact indicates that these signatures in zircons reflect well those in their parental bodies and are useful in identifying zircons derived from A‐type granite. Based on compilations of available data, zircons from A‐type granites can be clearly discriminated from other‐types of granites within Nb/Sr–Eu anomaly, U/Sr–Eu anomaly, Nb/Sr–U/Sr, and Nb/Sr–Ta/Sr cross‐plots. All indices used in these diagrams were selected based on the geochemical features of both zircon and whole rock of A‐type granites. Application of these discrimination diagrams to detrital zircons will likely provide further insights. For example, some Hadean detrital zircons plot in similar fields to A‐type granites, implying the existence of A‐type magmatism in the Earth's earliest history. Abstract : We examined trace element compositions of zircons extracted from the A‐type Ashizuri granitoids. Based on compilations of available data, zircons from A‐type granites can be clearly discriminated from other‐types of granites within Nb/Sr–Eu anomaly, U/Sr–Eu anomaly, Nb/Sr–U/Sr, and Nb/Sr–Ta/Sr cross‐plots.